Kinerja Balai Penyuluhan Pertanian (BPP) dan Dampaknya pada Perilaku Petani Padi di Sulawesi Selatan - Muh Hatta Jamil; Amri Jahi; Darwis S Gani; Ma'mun Sarma; I Gusti Putu Purnaba (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2012)
This research was aimed to know factors related to the action programs as a representation of BPP performance and relationship between factors that potentially increase BPP performance and their impacts to the behavioral changes of ricefield farmers in South Sulawesi. Population of this research were all BPP located in 15 districts (regencies) in South Sulawesi (176 sub-districts/150 BPP). Determination of samples used Slovin method, number of samples was 109 BPP located within 109 sub-districts. Research design was done based on the ex post facto with method design of survey and interviews using questionnaires. Design of data analysis used approach of Structural Equation Modeling (SEM) model applying LISREL program. Results of the research showed that variables of BPP development, BPP management, human resources, guided farmers, BPP resources, and BPP adaptation were significantly influencing the action programs as BPP representative performances with correlation coefficient (R2) was 0.72, the remaining 28 percent was affected by other factors outside of the study. Those factors directly influenced each others both insignificant and significant at α = 0.05. Besides that, they also indirectly influenced farmer behavior as much as 0.78 unit. The influence of action program as representation of BPP performances to the farmer behavior was indicated by correlation coefficient (R2) of 0.61, the remaining 39 percent was influenced by other variables outside of the study. Strategic implication of this research become important to the farmer behaviors, and to the development of BPP performances through action programs to a better direction by considering BPP development, BPP management, human resources, guided farmers, BPP resources and BPP adaptation.Keywords : Performances, development, management, resources, adaptation, action program, farmer behavior, BPP